The effect of consuming a liquid diet vs a solid diet 24-hr preexperimental trials on adherence in athletes - El-Chab, A.; Simpson, C.; Lightowler, H. (International Journal of Sport Nutrition and Exercise Metabolism, 2019)
Discrepancies in energy and macronutrient intakes between tests are apparent even when a solid prepackaged diet (Sdiet) is used to standardize dietary intake for preexperimental trials. It is unknown whether a liquid prepackaged diet (Ldiet) leads to improved adherence, resulting in lower variability in energy and macronutrient intakes. This study assesses the ability of athletes to replicate a diet when an Ldiet or Sdiet was used as a dietary standardization technique. In a cross-over design, 30 athletes were randomly assigned to either Sdiet or Ldiet. Each diet was consumed for two nonconsecutive days. Participants were instructed to consume all the meals provided and to return any leftovers. The coefficient of variation (CV) was calculated for each nutrient for the two methods and reported as the average CV. The Bland-Altman plots show that differences between Days 1 and 2 in energy and macronutrient intakes for both diets were close to zero, with the exception of some outliers. The %CV for Sdiet was higher than Ldiet (5% and 3% for energy, 5% and 3% for carbohydrate, 5% and 2% for protein, and 5% and 3% for fat, respectively). There was a strong positive correlation for energy and all macronutrients between Days 1 and 2 for both methods (r 0> .80; p < .05). Ldiet is an effective technique to standardize diet preexperimental trials and could be used as an alternative to Sdiet. Furthermore, Ldiet may lead to additional improvements in the compliance of participants to the diet and also decrease the cost and time of preparation.